2022
DOI: 10.1021/acsami.2c04759
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Multilayer Coating As Versatile Nanoarchitectonics for Customizing Various Bioinspired Liquid Wettabilities

Abstract: In last few decades, multilayer coatings have achieved enormous attention owing to their unique ability to tune thickness, topography, and chemical composition for developing various functional materials. Such multilayer coatings were mostly and conventionally derived by following a simple layer-by-layer (LbL) deposition process through the strategic use of electrostatic interactions, hydrogen bonding, host–guest interactions, covalent bonding, etc. In the conventional design of multilayer coatings, the chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 97 publications
0
11
0
Order By: Relevance
“…50 Moreover, the thickness and architecture of the prepared coating can be controlled strategically even with molecular precision. 50,68,[71][72][73] The construction of electrostatic interaction-driven multilayer assembly is found to be entropy-driven as the counter ions are released in this process. 74 Various advantages, such as (i) an easy and uncomplicated fabrication process, (ii) controlled modulation of multilayer thickness down to the nanometer scale and (iii) a surface-independent nature, make this fabrication method distinct and special from other approaches.…”
Section: Designs Of Stimuli-responsive and Chemically Reactive Multil...mentioning
confidence: 99%
See 3 more Smart Citations
“…50 Moreover, the thickness and architecture of the prepared coating can be controlled strategically even with molecular precision. 50,68,[71][72][73] The construction of electrostatic interaction-driven multilayer assembly is found to be entropy-driven as the counter ions are released in this process. 74 Various advantages, such as (i) an easy and uncomplicated fabrication process, (ii) controlled modulation of multilayer thickness down to the nanometer scale and (iii) a surface-independent nature, make this fabrication method distinct and special from other approaches.…”
Section: Designs Of Stimuli-responsive and Chemically Reactive Multil...mentioning
confidence: 99%
“…The design of reactive polymers and their reactive multilayer coatings provide a platform to modify multilayer coatings with selected chemicals to achieve desired properties. 72,89 Various reactive polymers like chitosan, branched poly(ethyleneimine) (BPEI), poly(2-vinyl-4,4-dimethylazlactone) (PVDMA), etc. are mostly involved in forming covalent crosslinking between two adjacent layers during the LbL deposition process.…”
Section: Materials Advances Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The physical properties of the supramolecular assemblies, such as wettability and elasticity can be modulated by intricate engineering of the building units. In this context, Manna et al reported a concise overview of the development of layer-by-layer (LbL) coatings with the design strategies and advantages of porous reactive multilayer coatings (RMLCs) toward achieving and controlling wettability properties . To improve the elasticity of such assemblies, Sun and co-workers demonstrated the preparation of a hydrogel membrane by complexing sulfonate-containing polyurethane (SPU) and poly­(acrylic acid) (PAA) with Zn 2+ ions (SPU-PAA/Zn).…”
mentioning
confidence: 99%